Partial Oxidation of Methane to Syngas Over Nickel-Based Catalysts: Influence of Support Type, Addition of Rhodium, and Preparation Method - Alvarez-Galvan, Consuelo; Melian, Mayra; Ruiz-Matas, Laura; Eslava, Jose Luis; Navarro, Rufino M.; Ahmadi, Mahdi; Roldan Cuenya, Beatriz; Fierro, Jose Luis G. (Frontiers in Chemistry, 2019)
There is a great economic incentive in developing efficient catalysts to produce hydrogen or syngas by catalytic partial oxidation of methane (CPOM), since this is a much less energy-intensive reaction than the highly endothermic methane steam reforming reaction which is the prominent reaction in industry. Herein, we report the catalytic behavior of nickel-based catalysts supported on different oxide substrates (Al2O3, CeO2, La2O3, MgO and ZrO2) synthesized via wet impregnation and solid-state reaction. Furthermore, the impact of Rh doping was investigated. The catalysts have been characterized by X-ray diffraction, N2 adsorptiondesorption at -196°C, temperature-programmed reduction, X-ray photoelectron spectroscopy, O2-pulse chemisorption, transmission electron microscopy and Raman spectroscopy. Supported Ni catalysts were found to be active for CPOM, but can suffer from fast deactivation caused by the formation of carbon deposits as well as via the sintering of Ni nanoparticles (NPs). It has been found that the presence of Rh favors nickel reduction, which leads to an increase in the methane conversion and yield. For both synthesis methods, the catalysts supported on alumina and ceria show the best performance. This could be explained by the higher surface area of the Ni NPs on the alumina surface and presence of oxygen vacancies in the CeO2 lattice, which favor the proportion of oxygen adsorbed on defect sites. The catalysts supported on MgO suffer a quick deactivation due to formation of a NiO/MgO solid solution, which is not reducible under the reaction conditions. The little carbon formation over the catalysts supported on La2O3 is ascribed to the very high dispersion of the nickel NPs and to the formation lanthanum oxycarbonate through which carbon deposits are gasified. The catalytic behavior for catalysts with ZrO2 as support depends on the synthesis method, however, in both cases, the catalysts undergo deactivation by carbon deposits.